Landscape-scale processes influence riparian plant composition along a regulated river. (January 2018) - Palmquist, Emily C.; Ralston, Barbara E.; Merritt, David M.; Shafroth, Patrick B.
Abstract: Hierarchical frameworks are useful constructs when exploring landscape- and local-scale factors affecting patterns of vegetation in riparian areas. In drylands, which have steep environmental gradients and high habitat heterogeneity, landscape-scale variables, such as climate, can change rapidly along a river's course, affecting the relative influence of environmental variables at different scales. To assess how landscape-scale factors change the structure of riparian vegetation, we measured riparian vegetation composition along the Colorado River through Grand Canyon, determined which factors best explain observed changes, identified how richness and functional diversity vary, and described the implications of our results for river management. Cluster analysis identified three divergent floristic groups that are distributed longitudinally along the river. These groups were distributed along gradients of elevation, temperature and seasonal precipitation, but were not associated with annual precipitation or local-scale factors. Species richness and functional diversity decreased as a function of distance downstream showing that changing landscape-scale factors result in changes to ecosystem characteristics. Species composition and distribution remain closely linked to seasonal precipitation and temperature. These patterns in floristic composition in a semiarid system inform management and provide insights into potential future changes as a result of shifts in climate and changes in flow management. Highlights: Temperature and seasonal precipitation influence riparian vegetation composition. Riparian communities can change significantly in response longitudinal gradients. Floristic changes can occur over relatively short distances along dryland rivers. Management and modeling need to account for differences in environmental conditions.